Examples of power transformers testing after outages and bad results of the chemical analysis of the oil sample - Milić, Momčilo; Jovanovic, Djordje; Dimitrijević, Marko (Proceedings, Electrical engineering institute "Nikola Tesla", 2023)
Power transformers represent one of the most important components in terms of production, transmission and distribution of electricity. Precisely for this reason, it is necessary to pay some attention in terms of preventive electrical measurements that should be done in order to have an adequate insight into their condition, avoid unwanted breakdowns and thus ensure stable and reliable operation of the entire power system. However, there are situations when power transformers fail due to various factors. In such cases, depending on which protection has reacted and preemptively switched off the observed transformer, and especially in the case of an outage due to the differential protection of the transformer, it is necessary to carry out certain tests before possible reconnection in order to assess the reason for the outage and the continued ability of the transformer itself to work. Electrical tests should be preceded by sampling oil from the transformer (and/or gas and oil from the Buchholz relay) for chemical analysis by the gas chromatography method. The results of the chemical analysis of the oil sample can express doubts about possible irregularities that may be a problem for further normal operation of the transformer and such situations are followed by certain electrical tests whose results in most cases will give a better insight into the state of the transformer itself. This paper will give examples of the results of electrical measurements made after power transformers were out of operation and measurements after bad results of chemical analysis of oil samples.